Short-Term Consequences of Pediatric Anti-cancer Treatment Regarding Blood Pressure, Motor Performance, Physical Activity and Reintegration Into Sports Structures - Keiser, Tina; Gaser, Dominik; Peters, Christiane; Oberhoffer-Fritz, Renate; Kesting, Sabine; von Luettichau, Irene (Frontiers in Pediatrics, 2020)
Background: Cardiovascular diseases in childhood cancer survivors are known late sequelae following treatment. Arterial stiffness, pulse wave velocity (PWV) and central systolic blood pressure (cSBP) are potential predictors to assess the status of cardiovascular health. Frequent inpatient stays and reduced physical activity (PA) during treatment can lead to noticeable impairments regarding motor skills and physical performance. The present study examined parameters of cardiovascular health, motor performance and the status of integration into sports structures shortly after cessation of treatment. Methods: A cross-sectional, monocentric study was conducted from April to June 2019. Participants (6-18 yrs, mixed cancer entities) during maintenance therapy and follow-up care were recruited. Peripheral and central systolic/diastolic blood pressure (pSBP, pDBP, cSBP) and PWV were assessed using the Mobil-O-Graph®. The MOON test (MOtor performance in pediatric ONcology) was used to scale motor performance. PA levels and status of integration into sports structures were assessed with a questionnaire referring to the KiGGS study. All measured data were compared to published reference values. Results: 40 participants (11.3±3.8 yrs, 50% female) were recruited 1.6±1.8 years post-treatment. PSBP (z-score: 0.87± 0.67, p=0.003), pDBP (0.83±1.94, p=0.033) and cSBP (≥8years: 0.60±1.29, p=0.011) were significantly increased compared to reference values. PWV was also elevated, but not significantly. Motor performance was reduced in almost all motor abilities. 36% of the examined group did not participate in physical education at school to the full extent. Only 17% reported one hour of daily moderate-to-vigorous PA as recommended for children and adolescents by the World Health Organization. Half of the participants were active sports club members before treatment, but one third did not resume their former membership. Conclusion: Increased cardiovascular parameters and impaired motor performance shortly after cessation of treatment, physical inactivity and low rates of integration into regular sports programs highlight the support needed. Young cancer patients should receive early support in coping with physical limitations preferably soon after diagnosis. Motor deficits could be reduced by applying targeted interventions. Furthermore, a regular sports therapy program during in- and outpatient care could increase engagement in PA to possibly counteract risk factors and improve cardiovascular health.